Redesain Rangka dan Peningkatan Kinerja Mesin Pencetak Kerupuk Berbasis Analisis FEA - Muhammad Dzikryan Rifanda; Muhammad Akhlis Rizza (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2026)
Cracker pr machines are widely used in small and medium-scale food industries. However, limitations in frame design and motor speed control often result in suboptimal machine performance. This study aims to perform a redesign of the upper conveyor frame, analyze the structural strength of the frame, and evaluate the effect of using a Variable Speed Drive (VSD) inverter on improving the production capacity of a cracker printing machine.The research method includes frame redesign, load calculation, and numerical analysis using the Finite Element Method (FEM) with SolidWorks Simulation. The applied loads consist of machine component weights and operational loads. In addition, performance testing was conducted by varying the motor rotational speed controlled by the VSD inverter to determine its effect on production output.The results show that the redesigned frame has a maximum displacement of 0.18 mm, a maximum stress of 8.9 MPa, and a minimum safety factor of 31, indicating that the structure is safe and operates within the elastic region. The implementation of the VSD inverter successfully increased the machine’s production capacity from the initial condition up to 78.5 kg/h. Based on these results, it can be concluded that the frame redesign and the application of a VSD inverter are effective in improving the performance and reliability of the cracker printing machine.